Tests on a non-clogging hydrokinetic turbine - Anyi, M.; Kirke, B. (Elsevier, 2015)
Hydrokinetic turbines (HKTs) are a promising technology for electrical power supply in small remote villages located in fairly flat, high rainfall country where other renewable energy technologies such as wind, solar and conventional micro-hydro are not suitable. However, clogging by floating debris has been identified as a major problem for HKTs in many waterways, and particularly in tropical rivers. To overcome this problem, an axial flow HKT has been designed using conventional wind turbine blade element theory and modified so as to minimize clogging by allowing one or more blades to swing back and forth in its plane of rotation. A 0.8. m diameter prototype has been constructed using low cost materials and simple tools. The final design was observed to shed long stringy algae and operate normally where a maximum coefficient of performance of 0.25 and a water-to-wire efficiency of just under 20% were achieved.